The causes of human sexual orientation - Cook, Christopher C. H. (Theology & sexuality, 2021)
Research on the causes of human sexual orientation has been marshaled in support of predetermined and opposing theological viewpoints. Whilst acknowledging that there is still much that is not known, the peer reviewed scientific literature clearly shows that a combination of genetic and environmental factors contribute to sexual orientation, with approximately one third of variance currently attributed to the former. Much of the known environmental influence appears to be intra-uterine and there is no currently convincing evidence that social environment plays a significant part. This body of evidence is relevant to theology. Greater attention should be given to critical interdisciplinary engagement of the theology and science of sexual orientation.